TIPOLOGI KELOMPOK ENTERPRENEURSHIP MINANGKABAU (Kasus Perempuan Pedagang di Pasar Nagari ) - Fitlayeni, Rinel (Jurnal Pelangi : Research of Education and Development, 2012)
The focus of this research to investigate the involment of women in villages in markettrading acticity in the economy, especially the old palant. reasonwomen are engaged intrading activities of market economy. The involvement of women in the villlages marketmeans to rebuild the local economy because the forerunner of entrepreneurship. Theinvolvement of women traders provide their own style to the typology groupsentrepreneurship in Minangkabau.The methodogy used a qualitative research with hermaneutik interpretative methods,sociology and historical studies.The result show that there are several groups entrepeneurship, first typology is thesmall traders (one man interprise), there are three categories : strongcapital, trader withoutcapital and wholesalers. The second typology is family enterprise, in the form of commercialbusiness unit or firm. The third typology small enterprise, which distuingishes the familyenterprise. This gruop has begun to expand business network not just to traders but alsoexport to other trading outside of the region.